Imidazole based ionenes, their blends with PBI-OO and applicability as membrane in a vanadium Redox flow battery - Struzynska-Piron, Izabela; Jung, Mina; Maljusch, Artjom; Conradi, Oliver; Kim, Sangwon; Jang, Jong Hyun; Kim, Hyoung-Juhn; Kwon, Yongchai; Nam, Suk Woo; Henkensmeier, Dirk (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
A new cationic ionene was synthesised from dibromoxylene and 2-(2,4,6-trimethylphenyl)benzimidazole. Even though the weight average molecular weight Mw reached values around 40,000 g/mole, no membranes could be prepared from this ionene, probably because of its rigid backbone. Blending with 33, 41 and 50 wt% PBI-OO gave access to self-supporting membranes. In comparison with pure PBI-OO, these membranes have a higher water uptake (30-50%) and show a chloride conductivity around 0.5 mS/cm at 60 degrees C. In the VRFB, the membranes absorb sulfuric acid, which increases the conductivity. Nevertheless, the voltage efficiency (VE) of PBI-OO was surprisingly low. Further analysis suggests that the polymer gets easily sulfonated, leading to ionic crosslinking and thus reduced conductivity. At OCV, the PBI-OO based membrane showed a very low potential degradation rate of 0.19 mV/h even over 280 h, while the OCV decreased 60% within 60 h for Nafion 212. Charge/discharge curves revealed that the coulomb efficiency (CE) decreases with increasing amount of the ionene, while the VE increases. This indicates a potential for improved membranes by blending PBI or its derivatives (responsible for high CE) with highly conducting ion exchange materials to increase the VE in comparison to the pure polymer.